Local Economic Development in the Post-Apartheid South Africa - Juta, Lusanda Beauty (Journal of Sustainable Development Law and Policy, 2025)
Concerted efforts have been geared towards development in the South African Post-apartheid era at local level. Studies have shown that local governments have recognized local economic development as a crucial tool for addressing development-related challenges. The extent to which the municipalities have ingrained the local economic development goal, however, has received little to no attention. Hence, this paper intends to fill the missing gap and answers the following questions: what are the key components of economic development at the local level in the post-apartheid era? To what extent has the local economic development stimulated growth and development with particular reference to small and medium scale enterprise? What are the donors’ approaches to local development and their critical challenges? Using the secondary sources of data collection, this paper reviews current level of economic development at local municipalities in South Africa. Thereafter, it examines the impact of the municipal government strategies designed to stimulate political and socio-economic development agenda at the local level in South Africa. This paper identifies strategic planning and local resources needed to address the local economic development in South Africa.